Quantification of total fetal brain volume using 3D MR imaging data acquired in utero. (29th November 2016) - Jarvis, Deborah; Akram, Rahim; Mandefield, Laura; Paddock, Michael; Armitage, Paul; Griffiths, Paul D.
Abstract: Objective: Interpretation of magnetic resonance (MR) imaging of the fetal brain in utero is primarily undertaken using 2D images to provide anatomical information about structural abnormalities. It is now possible to obtain 3D image acquisitions that allow measurement of fetal brain volumes that are potentially useful clinically. The aim of our current work is to provide reference values of total brain volumes obtained from a cohort of low risk fetuses with no abnormalities on ante‐natal ultrasonography and in utero MR imaging. Method: Images from volume MR acquisitions of 132 fetuses were used to extract brain volumes by manual segmentation. Reproducibility and reliability were assessed by analysis of the results of two subgroups who had repeated measurements made by the primary and a secondary observer. Results: Intra‐observer and inter‐observer agreement was high with no statistically significant differences between and within observers ( p  = 0.476 and p  = 0.427, respectively). The results of the brain volume assessments are presented graphically with mean and 95% prediction limits alongside estimates of normal growth rates. Conclusion: We have shown that fetal brain volumes can be reliably extracted from in utero MR (iuMR) imaging 3D datasets with a high degree of reproducibility. The resultant data could potentially be used as a reference tool in the clinical setting. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Measurement of fetal brain volume from iuMR imaging is a relatively new area of investigation and has been derived from motion‐corrected ultrafast 2D imaging, but there is limited published data because of small sample sizes. What does this study add? Fetal brain volumes can be derived from 3D iuMR acquisitions with a high degree of reproducibility using freehand segmentation. Our work demonstrated a quadratic model provided best fit to describe the changes of fetal brain growth in relation to gestational age, increasing from a mean value of 22.5 to 274.7 cm3 between 18 and 36 weeks gestation